Angiotensin II inhibits insulin signaling in aortic smooth muscle cells at multiple levels. A potential role for serine phosphorylation in insulin/angiotensin II crosstalk. - F Folli; C R Kahn; H Hansen; J L Bouchie; E P Feener (The Journal of Clinical Investigation, 1997)
To investigate potential interactions between angiotensin II (AII) and the insulin signaling system in the vasculature, insulin and AII regulation of insulin receptor substrate-1 (IRS-1) phosphorylation and phosphatidylinositol (PI) 3-kinase activation were examined in rat aortic smooth muscle cells. Pretreatment of cells with AII inhibited insulin-stimulated PI 3-kinase activity associated with IRS-1 by 60%. While AII did not impair insulin-stimulated tyrosine phosphorylation of the insulin receptor (IR) beta-subunit, it decreased insulin-stimulated tyrosine phosphorylation of IRS-1 by 50%. AII inhibited the insulin-stimulated association between IRS-1 and the p85 subunit of PI 3-kinase by 30-50% in a dose-dependent manner. This inhibitory effect of AII on IRS-1/PI 3-kinase association was blocked by the AII receptor antagonist saralasin, but not by AT1 antagonist losartan or AT2 antagonist PD123319. AII increased the serine phosphorylation of both the IR beta-subunit and IRS-1. In vitro binding experiments showed that autophosphorylation increased IR binding to IRS-1 from control cells by 2.5-fold versus 1.2-fold for IRS-1 from AII-stimulated cells, suggesting that AII stimulation reduces IRS-1's ability to associate with activated IR. In addition, AII increased p85 serine phosphorylation, inhibited the total pool of p85 associated PI 3-kinase activity, and decreased levels of the p50/p55 regulatory subunit of PI 3-kinase. These results suggest that activation of the renin-angiotensin system may lead to insulin resistance in the vasculature.